Integrated Metabolome and Transcriptome Analysis Reveals the Mechanism of Anthocyanin Biosynthesis in Pisum sativum L. with Different Pod Colors - Weijun Ye; Zejiang Wu; Dongfeng Tian; Bin Zhou (Agronomy, 2025)
Pea (Pisum sativum L.) is a significant source of dietary protein, starch, fiber, and minerals, offering health benefits and serving as both a green vegetable and dry grain. The pigment contents in pea pods with different colors and related genes are still unclear. We conducted an integrated transcriptome and metabolome analysis on three cultivars, including QiZhen (QZ) with green immature pods, FengMi (FM) with yellow immature pods, and ZiYu (ZY) with purple immature pods, to identify the key genes and metabolites involved in anthocyanin accumulation. ZY showed the highest total anthocyanin content compared with FM and QZ. Subsequent quantification revealed that four metabolites, including Delphinidin-3-O-galactoside, Delphinidin-3-O-(6″-O-xylosyl)glucoside, Cyanidin-3-O-galactoside, and Pelargonidin-3-O-(xylosyl)glucoside, were the most highly accumulated in the ZY cultivar, suggesting their role in the purple pigmentation of ZY pea pods. There were 49 differentially accumulated anthocyanidins in ZY vs. FM, 43 differentially accumulated anthocyanidins in ZY vs. QZ, and 21 differentially accumulated anthocyanidins in FM vs. QZ. These findings highlight the importance of the type and concentration of anthocyanin compounds, especially those based on delphinidin, cyanidin, and pelargonidin, in the development of purple pea pods. The transcriptomic analysis revealed that certain anthocyanin biosynthetic genes were expressed at higher levels in ZY than in FM and QZ. In ZY, the higher expression levels of five key genes (PAL, 4CL, CHS, F3H, and UFGT) resulted in elevated anthocyanin content compared to FM and QZ. Furthermore, the BSA-seq analysis identified a candidate region associated with purple color in pea pods, which is located on chromosome 6 and contains 21 DEGs. Sequence variation in KIW84_061698, which encodes a bHLH transcription factor, was identified as the key candidate gene controlling anthocyanin content. This study clarifies the molecular mechanisms behind pea pod coloration and identifies potential genetic engineering targets for breeding anthocyanin-rich sugar snap peas.